Studi Identitas Regional untuk Pariwisata Berkelanjutan di Kecamatan IV Koto Kabupaten Agam - Fadhillah, Abdul Khaliq; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
Tourism is growing rapidly globally, making an important economic contribution in Indonesia. However, it is necessary to focus on sustainable tourism that considers ecological and cultural aspects. This research aims to identify regional identity for sustainable tourism in IV Koto Sub-district, Agam Regency based on the potential of natural and cultural resources. The research method used in this research is quantitative and qualitative approaches, this research analyzes primary and secondary data to evaluate the attractiveness of natural attractions and cultural elements of interest to local communities. The results showed that the Great Wall of Koto Gadang was the natural attraction with the highest potential as a regional identity, while traditional ceremonies, particularly batagak gala, became the most significant cultural identity. The findings emphasize the importance of utilizing natural and cultural resources in a sustainable manner, involving the active participation of local communities in tourism development.